Directional Control of Wheel Syncronization in Vehicle Steer by Wire System - S. M. H., Fahami; Faiz, Mohd Turan (Penerbit UMP, 2022)
In conventional steering system a drive directly control the movement of the front wheel by control the steering wheel through a mechanical column shaft. However, in steer by wire (SBW) system, the front wheel is control by electronic function due to elimination of the mechanical column shaft and are replaced with several sensors and actutator. This paper propose a control algorithm to syncronize the front wheel angle accordance to steering wheel input angle. The models of SBW system are indentified. Two control method are compare which is a PID and LQR controller is used to control the front axle motor of front axle system. The effect with and without disturbace input are applied to analyze the robustess of the controllers. To investigate the effectiveness of the proposed control algorithm, the matlab tools software is used. And, based on the result shows, both controller able to control the front wheel angle, however method using the LQR control provide more better steering response